On the path to sociology with Professor Maria Aparecida de Moraes Silva - Ocada, Fabio Kazuo [UNESP] (Univ Sao Carlos, Dept Sociology Federal, 2024)
This paper discusses the training in Social Sciences and Sociology received over more than a decade of study at the College of Sciences and Letters of S & atilde;o Paulo State University (UNESP)- Campus Araraquara, under the guidance of Professor and Sociologist Maria Aparecida de Moraes Silva, a period during which he was possible to assist her in part of her research activities within the scope of rural sociology, raising a set of reflections that concern sociological theory, research methodology, the training and ethical stance of the researcher in the field of research and the profession of Sociology.
Keywords: sociology; education; work; migration; memory